THE USE OF ACTIVE STRATEGIES IN DEVELOPING LEARNING AND COMMUNICATION EXPERIENCES FOR CHILDREN WITH MDVI - ANDREA HATHAZI (Studia Universitatis Babes-Bolyai, 2010)
ABSTRACT. The quality and quantity of the learning experiences of a child with MDVI will determine motivation, participation, development, independence in the everyday functioning of the child. It is important that the learning experiences will focus on functional information, acquisition of abilities and skills, transfer and generalization of these skills, starting with an adequate understanding of these stages in the early development. Teachers and interveners should take into consideration how they organize these learning experiences so that the child benefit the most and all these are meaningful and create real and concrete opportunities. It is about assessment, meeting the child's learning needs, relating one activity, but also one skill to another so it gets meaningful, following the child's lead, but also using hand on hand exploration and communication.